2008
DOI: 10.17221/309-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary sources of roasted oilseeds on blood parameters and milk fatty acid composition

Abstract: ABSTRACT:The aim of this experiment was to investigate the effect of supplementing the basal diet with oilseeds on blood parameters and composition of milk fatty acids, especially conjugated linoleic acid (CLA). Forty-eight lactating Holstein cows in early lactation were used in a randomized block design. The cows in each group were fed the control basal diet (the control diet) or diets containing roasted soybean (RSB), roasted linseed (RLS), roasted sunflower seed (RSS), hulled roasted peanut (HRP) and roaste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
1
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 30 publications
3
25
1
6
Order By: Relevance
“…The proportion of saturated, monounsaturated and polyunsaturated fatty acids (SFA, MUFA and PUFA, respectively) was similar to that observed in other studies (e.g. Liu et al, 2008). The proportion of fatty acids synthesized de novo in the mammary gland (C6-C14) was higher by 10.5% in cows of the group MM than in those of the group OO.…”
Section: Discussionsupporting
confidence: 88%
“…The proportion of saturated, monounsaturated and polyunsaturated fatty acids (SFA, MUFA and PUFA, respectively) was similar to that observed in other studies (e.g. Liu et al, 2008). The proportion of fatty acids synthesized de novo in the mammary gland (C6-C14) was higher by 10.5% in cows of the group MM than in those of the group OO.…”
Section: Discussionsupporting
confidence: 88%
“…Daily average lactose production was similar in the "C" and "K" group (1.11 kg/head), this value was higher by 0.03 kg in the "O" group. Similar results were reported by Liu et al (2008), who fed various energy-rich oilseeds to dairy cows but they found no significant difference either in milk performance or in milk components. Zhai et al (2006) found no statistically significant differences in milk performance post partum except for urea concentration, which is similar to our experiment.…”
Section: Milk Performancesupporting
confidence: 86%
“…Crude protein and fat content of cow milk used in this study was similar to common milk obtained from Holstein cows (Brouček et al, 2004;Pešek et al, 2005;Liu et al, 2008).…”
Section: Chemical Analysesmentioning
confidence: 62%